THE IMPACT OF WORK LIFE BALANCE ON TURNOVER INTENTION: THE MEDIATING ROLE OF JOB ENGAGEMENT AMONG EMPLOYEES - Minal Saleem; Iqra Ashraf; Saman Shahzad (International Journal of Contemporary Issues in Social Sciences, 2024)
This study examined the influence of ethical leadership, employee ethics, ethical climate, and Work-life balance is a very important topic of employment. WLB means that employees achieve balance between work, family, and other life roles. Job engagement refers to an individual's enthusiasm and commitment to their work. Turnover intention means a conscious and deliberate desire to leave an organization. Work life balance and job engagement act as an important factor to ensure the growth of an organization .Hence difficulty to achieve balance between home and other life roles results in greater stress which in turn leads to more turnover intention. This study was designed to examine the impact of work life balance on Turnover intention: The Mediating role of Job engagement among employees.Work Life Balance was measured by Work Life Balance Scale, Job engagement was measured by Utrecht Job Engagement Scale (UWES) and Turn Over Intention Scale was used to measure turnover intention. A cross sectional study was conducted on a purposive sample (N=200) of employees from Private sector of Gujranwala, Pakistan. Findings of correlational analysis revealed a positive relationship between work life balance and job engagement and a significant negative relationship between job engagement and turnover intention. Regression analysis showed that work life balance significantly negatively predict turnover intention. Moreover mediation analysis revealed that job engagement doesn’t act as a mediating factor between work life balance and turnover intention .Overall findings of this study suggest that different strategies are required by employees to reduce turnover intention and to increase work life balance and job engagement .